Shared Decision-Making for Implantable Cardioverter-Defibrillators: Policy Goals, Metrics, and Challenges. Issue 4 (2021) - Rao, Birju R.; Merchant, Faisal M.; Howard, David H.; Matlock, Daniel; Dickert, Neal W.
Abstract: Shared decision-making has become a new focus of health policy. Though its core elements are largely agreed upon, there is little consensus regarding which outcomes to prioritize for policy-mandated shared decision-making.